2022
DOI: 10.2340/jrm.v54.87
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Knee–Ankle–Foot Orthosis on Functional Mobility and Activities of Daily Living in Patients with Stroke: A Systematic Review of Case Reports

Abstract: Objective: To synthesize available evidence from case reports regarding the efficacy of knee–ankle–foot orthosis (KAFO) on functional mobility and activities of daily living (ADL) in patients with stroke.Methods: The following databases were searched, based on the Population Intervention Comparison Outcome (PICO) model: PubMed, CINAHL, Scopus, Cochrane Central Register of Controlled Trials, PEDro, Web of Science, and Igaku Chuo Zassi (in Japanese). Methodological quality was assessed using the CARE checklist.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For these patients, KAFOs enable assisted gait training by immobilizing the knee joint in extension during the stance phase and preventing knee buckling ( 7 , 8 , 10 , 19 ). However, the effect of gait training with a KAFO on improving gait ability has not been fully investigated ( 15 ). Therefore, in the present study, paretic lower extremity muscle activity during assisted walking with a KAFO was investigated in acute hemiplegic stroke patients with severe gait disturbances, as well as its association with the improvement of walking independence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these patients, KAFOs enable assisted gait training by immobilizing the knee joint in extension during the stance phase and preventing knee buckling ( 7 , 8 , 10 , 19 ). However, the effect of gait training with a KAFO on improving gait ability has not been fully investigated ( 15 ). Therefore, in the present study, paretic lower extremity muscle activity during assisted walking with a KAFO was investigated in acute hemiplegic stroke patients with severe gait disturbances, as well as its association with the improvement of walking independence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the goal of gait training with a KAFO is to enable gait training with an AFO and eventually achieve independent walking with an AFO (7)(8)(9)(10)(11). However, the effectiveness of gait training with a KAFO on improving gait ability has not been fully investigated (15).…”
Section: Introductionmentioning
confidence: 99%
“…These can be in addition to knee collapse and backing of the knee due to gait posture in stroke patients [ 27 ]. Therefore, patients with stroke generally undergo gait training using knee-ankle-foot orthosis (KAFO) or ankle-foot orthosis (AFO) from the acute to sub-acute stages of stroke rehabilitation [ 28 , 29 , 30 ]. A previous study reported that the early wearing of KAFO was associated with higher recovery of ADL for stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically meaningful improvement in functional mobility promoted active rehabilitation and facilitated quick recovery in patients with stroke by KAFO were reported. 15 , 16 , 17 , 18 , 19 , 20 , 21 KAFO allowed patients to gain stability in paralyzed foot and walked with better dynamic balance. 21 ASAP employed a set of KAFO (Gait Innovation (Dial Lock) + GS Double Klenzak) which was designed to be shared in the hospital with quickly and easily adjustable circumference of thigh cuff, heights of lower leg cuff, knee joint and thigh cuff by the lever and slides.…”
Section: Methodsmentioning
confidence: 99%